2006
DOI: 10.1002/eji.200535514
|View full text |Cite
|
Sign up to set email alerts
|

Genetic vaccines against Ep‐CAM break tolerance to self in a limited subset of subjects: Initial identification of predictive biomarkers

Abstract: The epithelial cell adhesion molecule, Ep-CAM, has been historically considered a target of passive immunotherapy using monoclonal antibodies, and more recently, of a first Pox-vector-based cancer vaccine Phase I trial in colorectal cancer patients. To shed further light on the use of this antigen, we isolated the mouse and rhesus homologues of human Ep-CAM and explored different genetic vaccination modalities based on the use of adenoviral vectors as well as DNA electroporation (DNA-EP). Immune responses to E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Previous studies have shown successful immunotherapy for tumors in a cross-reaction between the xenogeneic homologues and self-molecules in a mouse model (43). In a recent study, mice vaccinated with Ad-hEp-CAM (epithelial cell adhesion molecule) or Ad-rhEp-CAM were protected from a tumor challenge with MC38-hEp-CAM cells; this showed that the immune response induced against hEp-CAM with both vaccines is sufficient to produce a biological antitumor effect (44). VLPs have the capacity to break self-tolerance to produce antibody responses against self-proteins expressed on them (45).…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies have shown successful immunotherapy for tumors in a cross-reaction between the xenogeneic homologues and self-molecules in a mouse model (43). In a recent study, mice vaccinated with Ad-hEp-CAM (epithelial cell adhesion molecule) or Ad-rhEp-CAM were protected from a tumor challenge with MC38-hEp-CAM cells; this showed that the immune response induced against hEp-CAM with both vaccines is sufficient to produce a biological antitumor effect (44). VLPs have the capacity to break self-tolerance to produce antibody responses against self-proteins expressed on them (45).…”
Section: Discussionmentioning
confidence: 92%
“…After 16 h medium was changed, and recombinant lentivirus vectors were harvested 48 h later. FACS analysis was conducted as previously described [15]. …”
Section: Methodsmentioning
confidence: 99%
“…One reason for the ability of xenogeneic antigen to break tolerance, as described in the paper in this issue of the European Journal of Immunology by Leonardo et al [8], is likely to be the presence of some foreign sequence in the xenogeneic antigen that is able to activate Th cells; however, this is rather a 'hit and miss' approach to breaking tolerance for therapeutic purposes since the degree of difference between self and xenogeneic antigen is often small and might be sufficient to induce an immune response only in a minority of patients with a suitable MHC Class II background. The variable performance of the mouse Ep-CAM vaccine in outbred mice described in the study by Lenardo et al [8] could reflect this heterogeneity.…”
Section: Importance Of T-cell Helpmentioning
confidence: 99%
“…One of these is electroporation, which has been shown to increase performance in large animals, including rhesus macaques [14]. Leonardo et al [8] use electroporation but combine it with a boost using a viral vector. The latter, however, introduces the problem of immunity against viral proteins which may be pre-existing and can block any boosting [15].…”
Section: Delivery Of Antigenmentioning
confidence: 99%
See 1 more Smart Citation